2015
DOI: 10.1038/cmi.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory of danger signals or environmental stimuli in mesenchymal stem cells: implications for therapeutic potential

Abstract: Mesenchymal stem/stromal cells (MSCs) possess some characteristics of immune cells, including a pro-inflammatory phenotype, an immunosuppressive phenotype, antibacterial properties and the expression of Toll-like receptor proteins. Here we show that, similar to immune cells, MSCs retain information from danger signals or environmental stimuli for a period of time. When treated with the pro-inflammatory factors lipopolysaccharide (LPS) or tumor necrosis factor-a (TNF-a), MSCs display increased expression of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…Studies have found that the exposure of MSCs to the pharmacological agent lipopolysaccharide (LPS) can increase their trophic effects and functional properties to defend against the harsh inflammatory environment [ 11 13 ]. Liu et al have confirmed that LPS-primed MSCs have a superior therapeutic ability to preserve skin flap survival in a diabetic rat model compared to unprimed MSCs [ 14 ]. However, it remains unclear how LPS-preconditioned MSCs (LPS pre-MSCs) resolve chronic inflammation and whether they may function by accommodating macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the exposure of MSCs to the pharmacological agent lipopolysaccharide (LPS) can increase their trophic effects and functional properties to defend against the harsh inflammatory environment [ 11 13 ]. Liu et al have confirmed that LPS-primed MSCs have a superior therapeutic ability to preserve skin flap survival in a diabetic rat model compared to unprimed MSCs [ 14 ]. However, it remains unclear how LPS-preconditioned MSCs (LPS pre-MSCs) resolve chronic inflammation and whether they may function by accommodating macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…This is corroborated by the finding that, in a similar fashion in mature human DCs, miR‐155 suppressed inflammatory cytokine production in response to LPS by targeting TAB2 . Interestingly, in another study with adipose tissue (AD)‐derived MSCs the increased levels of miR‐155 (and miR‐146a) after transient treatment with LPS or TNF‐α was retained for at least 5 days, suggesting that some miRNAs are involved in the regulation of a “short‐term memory” for danger signals .…”
Section: Micro‐rnas As Novel Modulators Of Tlr‐mediated Response In Mscsmentioning
confidence: 64%
“…Although these innate immune memory mechanisms have mainly been described in monocytes/macrophages and other immune cell types (reviewed in Netea et al, 2016), new studies are beginning to show that non-immune cells are also able to develop these memory-like responses (Hamada et al, 2019), including mesenchymal stem cells (Liu et al, 2016), hematopoietic progenitors (Kaufmann et al, 2018;Mitroulis et al, 2018) and skin epithelial stem cells (Naik et al, 2017). Concerning epithelial cells at mucosal surfaces, there is significant evidence for a priming event driven in a morphologyindependent fashion.…”
Section: Role Of Innate Immune Memory In Mucosal Surfaces Defensementioning
confidence: 99%